Implicit state estimators and their application to pole assignment controllers for systems with uncertainties - Chen, Xinkai; Fukuda, Toshio (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents implicit robust state observers for SISO minimum phase dynamical systems with arbitrarily relative degrees (with respect to the relation between the disturbance and the output). For systems with relative degree one, the state is expressed by the filters of the input and the output. No a-priori knowledge of the disturbance is required in this case.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka